On the Threshold of the Next Generation of Bible Translations: Issues and Trends - Naudé, Jacobus (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe aim of this paper is to describe the issues and trends facing the next generation of Bible translations. The paper starts with a description of the state of art of Bible translation before exposing features of the recently published Contemporary English Bible (1995), Das NeueTestament (1999), The Schocken Bible, Volume 1 (1995) and the Nieuwe Bijbel Vertaling (New Dutch Version) (2004). In the second part of the twentieth century a primary concern for meaning and readability has influenced the trend to produce translations which are more reflective of dynamic equivalence than formal equivalence. Examples are the Bible in Today’s English (1976), the Groot Nieuws Bijbel (Bible in Today’s Dutch) (1983) and the Nuwe Afrikaanse Vertaling (New Afrikaans Version) (1983). At the turn of the century translations with communication as their primary function were created (normally a rewriting of an existing translation in a modern vernacular by a single translator/editor), for example The Message in English (2000) and Afrikaans (2002). However, all these translations depend heavily on the reader’s ability to understand a written text. A new trend in Bible translation will take into consideration the requirements of the hearer, as well as those of the reader (the translation has to be read out aloud, heard and listened to). A shift away from the typical language usage of the Bible translations in the second half of the 20th century is the offing i.e. by instilling a new awareness in the minds of the readers to the sociocultural distance between them and the source culture.